Identifying hydroxylated copper dimers in SSZ-13 via UV-vis-NIR spectroscopy. Issue 9 (14th April 2022) - Göltl, Florian; Bhandari, Saurabh; Lebrón-Rodríguez, Edgard A.; Gold, Jake I.; Zones, Stacey I.; Hermans, Ive; Dumesic, James A.; Mavrikakis, Manos
Abstract : Potential active sites for the conversion of methane to methanol in Cu-exchanged SSZ-13 are identified using a combination of experimentally measured UV-vis-NIR spectroscopy and theoretical modeling. Abstract : Cu-Exchanged zeolites are promising materials for the selective conversion of methane to methanol. Their activity is attributed to the presence of small Cu-oxo and Cu-hydroxy clusters, but the nature of active centers in various zeolite structures is still under debate. In this contribution, we combine time dependent density functional theory with spin–orbit coupling to predict the optical spectra of various Cu monomers and dimers in SSZ-13. We furthermore compare theoretical results to experimental measurements and find that the presence of Cu-hydroxy dimers and Cu monomers could potentially explain the experimentally observed UV-vis-NIR spectra.